Promoting Moral and Spiritual Transformation: The Role of Pesantren Ramadan Programs in Preventing and Addressing Bullying in Educational Settings - Jenuri Jenuri; Deni Darmawan; Achmad Faqihuddin (STAI Hubbulwathan Duri, 2024)
This study investigates the impact of the Pesantren Ramadan program on fostering empathy and reducing bullying in educational settings, addressing the need for values-based interventions in character education. The importance of examining this program lies in its potential to shape moral and spiritual character among students, which is crucial for creating a safer, more respectful school environment. A qualitative research approach was employed, involving observations of Pesantren Ramadan activities, in-depth interviews with a purposive sample of 10 teachers experienced in the program, and document analysis from schools implementing this initiative. Data were analyzed thematically using NVivo 12 software to identify key patterns and themes related to empathy and bullying behavior. The program combines worship activities and social events designed to cultivate empathy and social responsibility. Findings demonstrate that students who participate in the program show enhanced empathy towards peers and a noticeable reduction in bullying incidents, attributed to activities such as communal prayers, iftar sharing, and community service, which reinforce values of compassion, mutual respect, and support. Additionally, as part of the program’s anti-bullying initiative, schools engage all members in a declaration against bullying, strengthening a collective commitment to respect and inclusion. The Pesantren Ramadan program, integrating both moral and spiritual activities, is shown to be an effective model for developing empathetic students and reducing bullying behavior. These findings suggest broader implications for educational policy and practice, offering a framework that could inspire similar values-based programs in other schools to enhance character education.